Kepercayaan Diri Mahasiswa Dalam Merespon Pada Proses Perkuliahan - Rini Hayati; Juli Yanti Harahap; Dewi Fitria (Departement of Mathematics Education, 2024)
Process the lecture activesness in responding can be observed throughout the course. The responses contribute to classroom dynamics, making it more active. Students' responses during lectures can be assessed, among other things, through their communication skills and self-confidence. This study aims to evaluate the level of students' self-confidence in responding during lectures. The method used is descriptive quantitative, which outlines the level of self-confidence in responding to lectures. The results indicate that 3% of students have low self- confidence in responding, 64% have moderate self-confidence, and 33% have high self-confidence. The average self-confidence score of students is 43.67, suggesting that the overall level of self-confidence is moderate. These findings highlight the need to focus on enhancing students' self-confidence to improve dynamics and engagement in the lecture process.